Mental health issues among unemployed and employed sports science graduates in Tunisia post-revolution - Chedlia Fitouri; Sofiane Souissi; Ghazi Racil; Hejer Ben Jomaa Ben Hsouna; Karim Chamari (Cogent Social Sciences, 2024)
This study investigates the relationship between employability and mental health among Tunisian sports science graduates post-2011 revolution, within the context of a prolonged socio-economic crisis and persistent unemployment lasting up to 10 years. The research included two studies. Study (1) quantitatively assessed 156 unemployed and 162 employed graduates for major depressive episodes (MDE), dysthymia, social phobia (SP), and generalized anxiety disorder (GAD). Study (2) qualitatively explored mental health experiences through semi-structured interviews with 20 participants (10 employed, 10 unemployed, balanced by gender). In Study (1), it was observed that unemployed individuals, especially older adults, women, and those experiencing long-term unemployment, exhibited elevated prevalence rates of MDE, dysthymia, and SP, while employed individuals exhibited higher GAD rates. Study (2) revealed widespread anxiety, fear, and low self-esteem among participants, driven by political and economic instability, career stagnation, and the devaluation of the sports profession. Many interviewees expressed a desire to work in Gulf countries due to attractive salaries and better job opportunities, while also calling for curriculum reforms and showing interest in entrepreneurship. The study concludes that employment alone does not guarantee mental health stability. Socio-demographic factors, economic issues, and political instability significantly affect mental health. To prevent brain drain and ensure mental well-being, developing economies must provide secure, opportunity-rich futures for young professionals. This research offers practical recommendations for policymakers in similar contexts.